2008
DOI: 10.1016/j.ijgo.2007.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial leukemia inhibitory factor as a predictor of pregnancy after in vitro fertilization

Abstract: Endometrial expression of LIF during the luteal phase can be used as a predictor of IVF success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 26 publications
(39 reference statements)
0
15
0
3
Order By: Relevance
“…It has been shown that women with higher endometrial LIF levels during midsecretory phase are more likely to get pregnant than are women with lower LIF levels. 75 Deceased uterine LIF levels are often associated with decreased fertility in humans; women with unexplained infertility have lower LIF levels compared with fertile women. 76,77 Furthermore, high endometrium LIF levels are associated with a successful implantation after an IVF cycle in IVF patients.…”
Section: Monographsmentioning
confidence: 99%
“…It has been shown that women with higher endometrial LIF levels during midsecretory phase are more likely to get pregnant than are women with lower LIF levels. 75 Deceased uterine LIF levels are often associated with decreased fertility in humans; women with unexplained infertility have lower LIF levels compared with fertile women. 76,77 Furthermore, high endometrium LIF levels are associated with a successful implantation after an IVF cycle in IVF patients.…”
Section: Monographsmentioning
confidence: 99%
“…[ [25][26][27] TGF-β During the menstrual cycle, the expression of the isoform transforming growth factor-beta (TGF-β) varies, being more intense in glandular epithelium during the late-secretory phase. Moreover, TGF-β may play a role in human implantation by promotion of adhesion of trophoblast cells to the ECM in in vitro assay.…”
Section: Il-6mentioning
confidence: 99%
“…Повышенная экспрессия мРНк LIf обнаружена в популяции лимфоцитов децидуальной оболочки, которые накапливаются в большом количестве в месте имплантации; это позволяет предполагать, что LIf опосредует взаимодействие между материнскими децидуальными лимфоцитами и цитотрофобластом. Serafini et al продемонстрировали, что у женщин с бесплодием и выраженной экспрессией LIf в середине лютеиновой фазы шансы на достижение беременности в 6 раз выше по сравнению с пациентками со сниженной экспрессией LIf [30]. Более того, у пациенток с СПя нарушена экспрессия ряда генов в период «окна имплантации» [31].…”
unclassified